Determinants of underweight among children under five years in Sungai Malang Community-Health Center - Tunggal, Tri; Ariyani, Eka; Rusmilawaty, Rusmilawaty; Prihatanti, Nur Rohmah; Santi, Mina Yumei (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: The most common nutritional problem in Indonesia is malnutrition. Children under five years are the age group that most often suffers from malnutrition. Underweight is a condition when a child's weight is below the normal range, indicated by a weight for age index of <-2 SD. Data from the health report for children under five years in North Hulu Sungai Regency, the percentage of underweight in Sungai Malang Community-Health Centers was 15.38% and in 2023 increase to 15.87%. Objectives: The aims of this research to determine the determinants of underweight among children under five years in Sungai Malang Community-Health Center, North Hulu Sungai Regency, South Kalimantan Province.Methods: A cross-sectional study was conducted involving 106 respondents selected through simple random sampling. Data were analyzed using univariate, bivariate (Chi-square), and multivariate (binary logistic regression) methods.Results: The prevalence of underweight was 33.96%. Significant determinants included low family income (OR=12.74; p=0.006), medium household size (OR=7.98; p=0.023), history of infectious diseases (OR=13.84; p=0.001), and low meal frequency (OR=47.19; p<0.001). Maternal education, child’s age, and sex were not significantly associated.Conclusions: Meal frequency emerged as the strongest determinant of underweight among children under five, followed by low family income, medium household size, and history of infectious diseases. The study recommends prioritizing efforts to improve meal frequency through community-based education, while encouraging health centers to actively promote early detection and prevention of underweight